Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan pada Rumah Makan RC21 Seafood Lahat (Studi Kasus) - Kasinem, Kasinem; Handayani, Melia; Hestin, Hestin; Pratiwi, Dini (Journal of Management and Bussines (JOMB), 2024)
The objectives of this to determine the influence of service quality on customer loyalty at the Balaiyasa Lahat Employee Cooperative, to determine the influence of customer satisfaction on customer loyalty at the Balaiyasa Lahat Employee Cooperative and to determine the influence of service quality and customer satisfaction together on customer loyalty at Balaiyasa Lahat Employee Cooperative. The sample for this research is the customers of the Balaiyasa Lahat Employee Cooperative, totaling 75 people. This research uses quantitative research, using data sources including: primary data, secondary data, population and sample. The data collection methods used were: observation, interviews and distributing questionnaires to a number of respondents. As well as using validity and reliability measuring instruments, prerequisite analysis tests, then using data analysis methods using multiple regression analysis, hypothesis testing in the form of t tests and F tests, as well as correlation coefficients and coefficients of determination. Data analysis in this research used SPSS 23.0. From the results of this research, it can be seen partially with the t test that the service quality variable with t calculated > from t table or 13.873 > 2.000, is rejected, accepted, this shows that there is a significant influence between the service quality variable and the customer loyalty variable. And the customer satisfaction variable with t count > from t table or 11.133 > 2.000, then it is rejected, accepted, this shows that there is a significant influence between the customer satisfaction variable and the customer loyalty variable. Keywords: Service Quality, Customer Satisfaction, Customer Loyalty